Zinc-Phosphorus Interaction on Growth and Nutrient Uptake by Maize (ZEA Mays L.) - Totawat, K L; Saeed, Mohammed (Annals of Arid Zone, 2016)
Field experiment on zinc-phosphorus in teraction on the yield and quality of maize (Zea maysL.) was undertaken in kharif 1985 on silty clay loam soil. An increase in the level of zinc upto 45 kg ZnS04 ha-1 and phosphorusupto 30 kg P ha-1 have increased their available status in soil.Foliar sprayof zinc at 15 kg ZnS04 ha-1 in conjunction with phosphorus at 30 kg P ha-1gave significantly higher grain and stalk yield, nutrient uptake and quality of the maize crop. Foliar spray of zinc is superior mode of zinc fertilization.